Cashua : integrating semantics and content-based networking for context distribution - Power, Ruaidhrí (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2009)
To support a vision of ubiquitous computing where computers fade into the background, context systems must provide information to highly mobile people and devices in ubiquitous computing environments. In these environments, each person is served by many applications hosted by many different devices. These applications will be heterogeneous, as it is unlikely that a single standard model for context will emerge. The system must support dynamic routing of context information to allow user mobility. Finally, the system must support not-yet-developed applications, with new context models. The Cashua system uses ontology models of context for two purposes - to manage heterogeneity and to route context information over a content-based network (CBN). The CBN is used to route queries and results, but also routes mappings between context models, allowing heterogeneous applications to communicate where an appropriate mapping between models has been provided on the network. By coping with both heterogeneity and dynamic environments, this work advances the state of the art, using a novel approach to context dissemination which is evaluated using a number of experiments and case studies.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin